Menumbuhkan Semangat dan Motivasi Belajar Bahasa Inggris dalam Menghadapi Revolusi Industri 4.0 pada Sekolah Dasar di Phatnawitya dan Darul Muhmin, Thailand Selatan - Widia Aulia Rahmah; Jericho Aditya Vandy; Rizky Titis Agustianto; Sri Harini; Endang Silaningsih; Erni Yuningsih; Indra Cahya Kusuma; Didi Didi (Pusat Riset dan Inovasi Nasional, 2025)
This service activity is motivated by the difficulties of primary school students in learning English. This activity aims to promote enthusiasm and motivation to learn English among primary school students in the light of Industrial Revolution 4.0 at Phatnawitya School Yala and Darul Muhmin School Satun, Southern Thailand. The learning media implemented is supported by the use of technology such as television, speakers, laptops, etc. The delivery method consists of preparation, implementation, monitoring and evaluation phases. The results of the classroom activities for the students supported by technological assistance result in the students being more enthusiastic, excited and motivated during the English learning process.